Dissecting the cardiac cell landscape in myocarditis. (3rd October 2022) - Gil-Cruz, C; Perez-Shibayama, C; Naegele, M; Cheng, H W; Luetge, M; Frischmann, K; Joachimbauer, A; Parianos, D; Flammer, A J; Ruschitzka, F; Ludewig, B; Schmidt, D
Abstract: Introduction: Myocarditis is the prototypical cardiac inflammatory disease, with an incidence of 20–30 per 100000 individuals. Acute myocarditis potentially develops into lethal inflammatory cardiomyopathy in a substantial fraction of patients, rendering myocarditis and its sequelae the underlying reason for many heart transplants and 10–20% of cardiovascular sudden deaths in young adults. Different pathological routes had been described to lead to myocardial inflammation (eg. viral, bacterial or parasitic infection, autoimmune processes, toxins). Moreover, genetic predisposition and environmental factors such as the microbiome influence the progression of the disease. Therefore, it is plausible that the inherent complexity of the disease hampers the elucidation of effective therapeutic interventions because the molecular mechanisms underlying this severe heart condition are – to a large extent – incompletely understood. Therefore, it is important to elucidate the molecular pathways governing the interplay between immune cells and stromal cells in the cardiac microenvironment in myocarditis. Methods: To dissect the processes involved in myocarditis progression, we took advantage of the T cell receptor transgenic mouse model of spontaneous autoimmune myocarditis (TCRM) were all mice develop acute myocarditis around 4 weeks of age that progresses to lethal dilated cardiomyopathy in 50% of the mice. To analyse the mechanisms involved in cardiac inflammation in mouse and human patients, we used single cell and single nucleus transcriptomic approaches in combination with high dimensional flow cytometry, confocal microscopy and echocardiographic analysis of the cardiac function. To examine the cardiac landscape in humans we applied the same analysis methodologies to right ventricle endomyocardial biopsies from myocarditis or heart transplantation patients (control). Results: Our analysis shows that dynamic changes occur in the cardiac microenvironment during the course of myocarditis; these changes involve not only the recruitment of immune cells expressing pro-inflammatory signatures to the myocardium (T cells, inflammatory monocytes, neutrophils) but also the alteration of transcriptional programs in non-immune cells including fibroblast, endothelial cells and cardiomyocytes. The analysis of endomyocardial biopsies from myocarditis patients revealed similar changes in the cardiac cell population's transcriptome. Conclusion: Our study reveal that the transcriptional landscape of cardiac cells is strongly influenced by the inflammatory microenvironment. Notably, during the acute phase of myocarditis pathways supporting inflammation and fibrosis overrule circuits involved in cardiac homeostasis. Moreover, we show that the analysis of endomyocardial biopsies by single-nucleus RNAseq represents a powerful tool to unveil the processes involved in cardiac diseases. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): ERC personal grant to Burkhard Ludewig